The Eliza effect and its dangers: from demystification to gender critique. - Dillon, Sarah (Journal for Cultural Research, 2020)
This essay provides a gender critique of the Eliza effect. It delineates the way in which the Eliza effect is operationalised in AI research even as it is ostensibly demystified, for example, in the writings of Douglas Hofstadter and Joseph Weizenbaum. It then exposes the gendered assumptions embedded in the nomenclature used to name this misperception of the computer as having capabilities equivalent to the human. It traces the genealogy of that nomenclature back through Weizenbaum's ELIZA, to George Bernard Shaw's Pygmalion. A close reading of the play is deployed in order to reveal the structural inequities of gender, class, and who or what gets to be human, that are both explored in the play and encoded in the operation and operationalisations of the Eliza effect. It concludes by attending to that operation and operationalisation in relation to today's Virtual Personal Assistant's, and makes a case for the importance of critique in order to expose the inequitable structures of power obscured and compounded by the Eliza effect – both its name, and that which it names.